2017
DOI: 10.1302/2046-3758.64.bjr-2016-0224.r1
|View full text |Cite
|
Sign up to set email alerts
|

The role of miR-320a and IL-1β in human chondrocyte degradation

Abstract: ObjectivesThis study aimed to explore the role of miR-320a in the pathogenesis of osteoarthritis (OA).MethodsHuman cartilage cells (C28/I2) were transfected with miR-320a or antisense oligonucleotides (ASO)-miR-320a, and treated with IL-1β. Subsequently the expression of collagen type II alpha 1 (Col2α1) and aggrecan (ACAN), and the concentrations of sulfated glycosaminoglycans (sGAG) and matrix metallopeptidase 13 (MMP-13), were assessed. Luciferase reporter assay, qRT-PCR, and Western blot were performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…A few years ago, Meng et al [ 82 ] also identified miR-320 as a regulator of MMP13 , where NF-κB and MAPK activation was shown to downregulate miR-320 expression. This conclusion was later extended by Jin et al [ 83 ], who showed that overexpression of miR-320a, which targets the pre-B-cell leukemia transcription factor 3 ( PBX3 ) gene, increased MMP-13, whereas PBX3 and the proteasome inhibitor, MG132, suppressed the effects of miR-320a on the expression of COL2A1 , ACAN (i.e., the aggrecan gene), sulfated glycosaminoglycans, and MMP-13. Moreover, miR-105 was also found to be important for the fibroblast growth factor-2 (FGF2)-induced gene expression of ADAMTS4 , 5 , 7 , and 12 [ 84 ].…”
Section: Specific Mirs: Role In Chondrocyte Signaling Pathways Apmentioning
confidence: 87%
“…A few years ago, Meng et al [ 82 ] also identified miR-320 as a regulator of MMP13 , where NF-κB and MAPK activation was shown to downregulate miR-320 expression. This conclusion was later extended by Jin et al [ 83 ], who showed that overexpression of miR-320a, which targets the pre-B-cell leukemia transcription factor 3 ( PBX3 ) gene, increased MMP-13, whereas PBX3 and the proteasome inhibitor, MG132, suppressed the effects of miR-320a on the expression of COL2A1 , ACAN (i.e., the aggrecan gene), sulfated glycosaminoglycans, and MMP-13. Moreover, miR-105 was also found to be important for the fibroblast growth factor-2 (FGF2)-induced gene expression of ADAMTS4 , 5 , 7 , and 12 [ 84 ].…”
Section: Specific Mirs: Role In Chondrocyte Signaling Pathways Apmentioning
confidence: 87%
“…The Wilcoxon test following Bonferroni adjustment was performed for VAS analog, WOMAC score, Lequesne Index score, TUG test, and SLS test between baseline and after 1 month, 3 months, and 6 months follow-up [ 21 ]. Independent t -test [ 22 ] following Bonferroni adjustment [ 21 ] was performed for VAS analog, WOMAC score, Lequesne Index score, patient satisfaction, and adverse effects between groups at 1-month, 3-months, and 6-months follow-up. The Mann-Whitney U test following Bonferroni adjustment was performed for the TUG test and the SLS test between the groups at 6-month follow-up [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, a microarray analysis has shown overexpression of miR-320a in whole bone tissue from women with osteoporotic fracture [2, 3]. Moreover, miR-320a is elevated in osteoarthritic cartilage tissue and chondrocytes [4], highlighting its potential functionality in the musculoskeletal system. This miRNA has been reported to have multiple mRNA targets and to regulate different pathways in various cell types.…”
Section: Introductionmentioning
confidence: 99%